TYPICAL METHODS OF COMMITTING CORRUPTION CRIMES COMBINED WITH OBTAINING ILLEGAL BENEFIT (Bulletin of criminological association of Ukraine, 2025)
The article emphasizes that corruption-related crimes involving illicit gain are characterized by typical methods of preparation, direct commission, concealment, and criminal technologies. The following typical methods of such corruption-related crimes are identified and described: 1) preparation methods: building connections (establishing and maintaining trust with officials who can facilitate the implementation of a corruption scheme); document preparation (falsification or creation of fake contracts, acts, or reports necessary to disguise future criminal actions); identifying vulnerabilities in potential victims (analyzing the financial or legal status of potential victims to later exploit these circumstances in corruption schemes); scheme planning (developing an action mechanism, including involving intermediaries, determining benefit transfer channels or methods of legal disguise); 2) methods of direct commission: abuse of official position (blocking legal processes, delaying permits, creating bureaucratic obstacles, or providing unofficial preferences); psychological pressure (manipulation, blackmail, hints of possible problems that force the victim to agree to the perpetrator’s terms); masking as legal actions (using fictitious contracts, "charitable contributions," fictitious employment, or false agreements); using intermediaries (involving third parties to complicate the identification of perpetrators and the documentation of crimes); using the "corruption rent" scheme (systematic receipt of benefits in the form of tariffs, percentages, or monthly payments for obtaining services or avoiding obstacles); 3) methods of concealment: falsification of accounting and reporting (making changes to documents that hide the fact of illicit enrichment); destruction of evidence (destruction of documents or material evidence that may indicate criminal activity); transferring persons involved in the crime to other positions or workplaces; staging legality (signing acts of acceptance-delivery for services or completed works that were not actually provided); official forgery (creating fictitious documents that conceal other crimes, e.g., abuse of power or bribery).
Keywords: criminalistic characteristics; corruption; corruption crimes; illicit enrichment; typical methods; methods of preparation; methods of direct commission; methods of concealment; criminal technologies